Norman Doe’s Proposed Typology of Church-State Interaction and Its Applicability to Comparative Constitutional Law Research - Turonis, Vytis (Teisė, 2022)
This article examines the types of church-state interaction and their main features found in Lithuanian and foreign legal literature and highlights the three-tier typology of church-state interaction as formulated by Norman Doe, revealing the constitutional problems of its applicability and assigning specific theoretical types to individual states.
Keywords: Church; State; Types of interaction between church and state; Separation of church and state; State Church; Church and state cooperation